Cosmogony and Cosmology in Korean Confucian Historiography. Based on the Samguk Sagi by Kim Busik - A. V. Solovyov (Концепт: философия, религия, культура, 2024)
This research aims to test the assumption, long-established in Oriental studies, that Confucian philosophy and, therefore, historiography, focused primarily on the specific and rational tasks of social management and government, which tend to ignore the issues of cosmogony, instead replacing it with cosmology. However, in recent times, claims about the paramount rationality of Confucian chronicles have been questioned. These doubts are of relevance in relation to the Korean official Confucian chronicle the Samguk sagi (Historical Records of the Three Kingdoms). Juxtaposing its text with other Korean sources, this article identifies three layers in which cosmogonic motifs and elements of cosmogonic myths can be found. These elements are observed in the stories about the founders of states as cultural heroes, in the approach of the historiographer Kim Busik to the presentation of the history of dynastic cycles (the emergence–bloom–decline–fall of the state), and in the biographies of various historical characters, which are included in a special biographical section of the chronicle. The composition of these biographies partially reproduces the cosmogonic model of the cycle of the hero’s transformations developed by Joseph Campbell. In the annalistic narrative, cosmogonic motifs are closely intertwined with cosmological motifs, forming a kind of a binary yin-yang monad. Kim Busik's Confucian historiographical rationalization does not reject myth entirely, integrating into the historical-political moralizing narrative those elements that correspond to the canon of historiography and their significance for the history of the country and the people. The very process of such integration requires serious efforts from the historiographer, since myths sometimes resist such reappropriation. As a result, many mythological stories are discarded, leaving in the historical narrative either the strongest, most significant elements, that in a sense overpower the canon, or those that resonate with the mythological basis of the canon itself.